Simultaneous wastewater treatment and power generation with single chambered up-flow membrane-less microbial fuel cell
Microbial fuel cell (MFC) is a technology that can convert chemical energy into electrical energy from biomass. MFC is also one of the promising technology to generate sustainable green bioenergy. The development of MFC technologies have been expanded to various application, such as wastewater treatment, specific inorganic pollutant treatment, sediment bioremediation and biosensor. This thesis addressed the potential of an up-flow membrane-less (UFML) MFC that used for wastewater treatment with an enormous variety of configurations and working parameters. The primary objective of this study is to examine the potential and the mechanism of the novel UFML MFC by using various carbon material as aqueous biocathode. Further investigation was conducted to evaluate the effect of the biofilm formation on different carbon material surface morphology based on performance of power output and chemical oxygen demand (COD) reduction in UFML MFC. Carbon flake, Pt-loaded carbon paper, carbon plate and carbon felt were used as aqueous biocathode. The voltage output for the carbon flake cathode (384 ± 16 mV) was comparable to the Pt-loaded carbon paper cathode (399 ± 9 mV), which is unexpected. The COD reduction efficiency for all cathode materials at the anode region and effluent were achieved as high as 75% and 85%, respectively. The surface area and surface morphology of the cathode material may influence the ability of microbial attachment and electron transfer. The results suggested that the power generation and the COD reduction were influenced by the cathode material. Besides, UFML MFC was also used to further explore the potential and the mechanism between biodegradation of Acid Orange 7 (AO7) and generation of bioelectricity. The decolorization efficiency of AO7 was up to 96%. Overall voltage output was affected by the increased dosage of AO7. However, the increased dosage of AO7 and continuous 24- h flow could help to lower down the other anaerobic microbial activities and consequently caused more available electrons which can be used by AO7 decolorization and electricity generation. Furthermore, the decolorization of AO7 at cathode region indicated that the oxygen and azo dye were both competed for electron acceptor. Based on the UV–visible spectra analysis, the breakdown of the AO7 azo bond into more toxicity aromatic compounds in anaerobic condition were confirmed. Nonetheless, these aromatic compounds can be further degraded into short chain aliphatic acids and lastly decomposed into carbon dioxide and water. In additional, the intermediates listed in the proposed plausible biodegradation pathway were partially identified. These results proved that the combination of anaerobic-aerobic in UFML MFC was able to completely mineralize the AO7. Lastly, the new enhanced up-scaled UFML MFC (SUFML MFC) was fabricated with innovative anode configuration (cube carbon felt and linked carbon felt). This reactor was used to examine the overall performance of power output with different hydraulic retention time (HRT) and electrode spacing distance. The results proved that the linked anode was better in flow pattern and mass transfer, providing overall better voltage output during stationary phase at all different HRT setup.